«Tierra de nadie»: Estado y desarrollo humano en Madre de Dios - Fuentes, Alejandra (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
Traditionally, one of the most important questions in social sciences has been one that asks about differences in levels of development (between regions, countries and sub-national units). However, it is only in the last decades that development has begun to be understood from a perspective centered on people and, particularly, on their well-being and freedom to live the life they choose to live. This article argues why a region like Madre de Dios—characterized by its geographical complexity, illegal economies, high rates of human trafficking and other problems—has managed to maintain relatively successful levels in the Development Index over time. Human. From a sub-national perspective, it is proposed that in this region three different levels of human development coexist in three different areas of the territory that are overshadowed by regional measurement. These three differentiated levels, in turn, are the result of different patterns of relations between State and society based on two conditions: (1) the type of non-state actors and (2) the nature of the interaction.

Tradicionalmente, una de las preguntas más importantes en las ciencias sociales ha sido aquella que indaga por las diferencias en los niveles de desarrollo (entre regiones, países y unidades subnacionales). Sin embargo, solo en las últimas décadas se ha empezado entender el desarrollo desde una perspectiva centrada en las personas y, particularmente, en su bienestar y libertad para vivir la vida que elijan vivir. En esta línea, el presente artículo indaga por qué una región como Madre de Dios —caracterizada por su complejidad geográfica, economías ilegales, altos índices de trata de persona y otras problemáticas— ha logrado mantener en el tiempo niveles relativamente exitosos en el índice de desarrollo humano. Desde una perspectiva subnacional, se plantea que en dicha región coexisten tres niveles diferenciados de desarrollo humano en tres zonas distintas del territorio que son eclipsados por la medición regional. Estos tres niveles diferenciados, a su vez, son el resultado de distintos patrones de relaciones entre Estado y sociedad basados en dos condiciones: (1) el tipo de actores no estatales y (2) la naturaleza de la interacción.
«No one’s territory»: State and human development in Madre de Dios
Keywords: Amazonía; Desarrollo; Estado; Territorio; Actores; https://purl.org/pe-repo/ocde/ford#5.04.00